Phytogenic Feed Additive Influences on the Growth Performances, Serum Lipid Profile, Liver Functions and Antibacterial Activity of Broiler Chicks - Abedin, M.T.; Sujon, M.N.; Islam, M.N.; Sadiq, S.R.; Sayed , M.A. (International Journal of Poultry Science, 2021)
Objective: This investigation was performed to explore the combined effect of buckwheat (BW), black cumin (BC) and honeyweed (HW) supplemented diet on growth performances, blood metabolites and intestinal microflora of broiler chicks for the production of safe meat. Materials and Methods: A total of 60 day-old chicks (Cobb-500) were divided into four groups viz. T1(Commercial control, CC), T2 (Formulated Feed, FF+10% BW), T3 (FF+10% BW+1.5% BC+5% (w/v) HW powder), T4 (FF+10% BW+3% BC+5% (w/v) HW powder) in complete randomized design with three (3) replications, each of which contain 5 birds. Results: At the end of the 30 days, T3 diet significantly (p<0.05) showed the lowest FCR, mortality rate and the highest body weight gain. Interestingly, T3 diet improved the blood metabolites remarkably (p<0.05). Surprisingly, histological study revealed the low deposition of fat in liver in case of BW, BC and HW supplemented feed. Furthermore, T3 supplemented feed also suppressed total viable bacteria in the feces and methanol extract, water extract of combined BW, BC, HW also showed the inhibition zone against the bacteria. Conclusion: T3 diet could be used for safe and quality poultry meat production as it showed good FCR and low mortality rate as compared to control treatment.